Outsourcing of services and regional impact on employment - Peter Sjoholt (European Regional Science Association (ERSA), 1998)
This paper focuses on the issue of organisation and purchase of services by public authorities (mainly municipalities) and large corporations (mainly one company towns). It deals with restructuring of service provision, notably outsourcing of different types of services from institutions and corporations and the concomitant regional and local impact upon employment. It is hypothesised that effects may be both positive and negative, depending on the types of service and location of the buyers. The discussion is theoretical, viewing outsourcing in its preconditions and effects as outcomes of economic,social,cultural and political factors and forces in society at large. Some selected empirical cases from Norway are included, however, in order to analyse more closely beneficial or adverse regional employment effects.
Keywords: 330